Soil nitrous oxide emissions from Eucalyptus plantation in Argentina - Alvarez, Carina Rosa (2020)
Nitrous oxide has a key effect on global climate development and 53% of N2O total annual emissions are related to fluxes from the soil. Land use and soil characteristics affect N2O emissions. There are not enough assessments in Argentina to quantify N2O emissions from commercial forest plantations. This research aimed at quantifying N2O fluxes from Eucalyptus grandis plantations and at identifying factors explaining emission variability. The study was carried out in Gualeguaychú, Entre Ríos Province, Argentina (33°1′17″S, 58° 13′37″W) on Eucalyptus grandis plantations in four different situations: at two ages (2–4 yr and 8–10 yr), on two contrasting texture soils (coarse and fine), and on a medium-textured sodic soil in a natural forest (shrubland). Greenhouse gas emissions (N2O and CO2) were measured 12 times between August 2016 and October 2017. Emission rates and annual N2O emissions were low in all evaluated treatments (average emission rate: 2.62 µg N2O-N m−2 h−1, and average annual emission: 0.226 kg N2O-N ha−1 year−1 ). These rates are considerably lower than those of agricultural situations in the same region. This can be explained by the null use of nitrogen fertilization and by the absence of atmospheric nitrogen- fixing crops in forestry plantations. The use under natural forest showed the highest cumulative annual emissions (0.698 kg N2O-N ha−1 year−1 ) possibly because of its woody leguminous species composition and its higher soil water content. N2O emissions in fine 2-4y, coarse 2-4y, and in coarse 8-10y were in average 0.0896 kg N2O-N ha−1 year−1 with no statistically differences between them. The fine 8-10y N2O emissions did not differ from the natural forest neither from the other treatments (0.261 kg N2O-N ha−1 year−1 ). Soils with higher clay content showed a trend toward higher N2O emissions than sandy soils. NO3-N level in soil was the variable that best explained N2O-N emissions (p < 0.001). Since nitrate content and CO2 emission were the variables most associated with nitrous emissions, it can be hypothesized that in clay soils greater emissions can be originated by higher nitrification as a result of their higher organic matter content or due to a deni trification provoked by the depletion of oxygen in a high consumption respiration process, and poor oxygen renewal caused by the increased amount of micro-aggregates and pores.